2012
DOI: 10.4161/auto.8.2.18807
|View full text |Cite
|
Sign up to set email alerts
|

The role of autophagy in endoplasmic reticulum stress-induced pancreatic β cell death

Abstract: Shang-Ha Pan (2012) The role of autophagy in endoplasmic reticulum stress-induced pancreatic β cell death, Autophagy, 8:2,[158][159][160][161][162][163][164] DOI: 10.4161 Keywords: autophagy, endoplasmic reticulum stress, pancreatic beta cell, free fatty acid, glucagon like peptide-1In pancreatic b-cells, the endoplasmic reticulum (ER) is the crucial site for insulin biosynthesis, as this is where the proteinfolding machinery for secretory proteins is localized. Perturbations to ER function of the b-cell, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 77 publications
1
40
0
Order By: Relevance
“…In fact, transgenic mice lacking autophagy in their b-cells exhibit decreased b-cell mass and an aberrant response to glucose stimulation. Moreover, inhibition of autophagy increases the vulnerability of b-cells to cytotoxic effects (Yin et al, 2012). It has therefore been suggested that autophagy is essential to maintain the structure, mass, and function of b-cells.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, transgenic mice lacking autophagy in their b-cells exhibit decreased b-cell mass and an aberrant response to glucose stimulation. Moreover, inhibition of autophagy increases the vulnerability of b-cells to cytotoxic effects (Yin et al, 2012). It has therefore been suggested that autophagy is essential to maintain the structure, mass, and function of b-cells.…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported marked autophagy induction during treatment of human pancreatic islets with palmitic acid, but not with glucose [140]. Thus far, relatively little is known about the exact interplay between autophagy and ER stress, but most of the evidence is in favor of targeting autophagy as a protective mechanism of b-cells to ameliorate ER stress [141].…”
Section: Diabetesmentioning
confidence: 99%
“…These findings suggest that ER stress might be upstream of oxidant stress in hypertension. In addition, ER stress is often associated with autophagy (15), and the relevance of this for cells in the SFO is unknown. Finally, ER stress in pathological settings is usually associated with apoptotic cell death.…”
Section: Figurementioning
confidence: 99%